Cardiomyocyte-Derived Exosomes: Biological Functions and Potential Therapeutic Implications - Yu, Hui; Wang, Zhanli (Frontiers in Physiology, 2019)
Exosomes, which are membrane-enclosed nanovesicles released by almost all cell types, have been recognized to play important roles in mediating cell–cell communication. In recent years, the physiological and pathological effects of exosomes on cardiovascular disease have been extensively studied. Exosomes can transfer proteins, mRNAs, microRNAs, and other bioactive molecules to recipient cells to influence their biological properties. In recent years, accumulating evidence has suggested that cardiomyocyte-derived exosomes play an important role in the progression of cardiovascular disease. Here, we summarize the functional roles of cardiomyocyte-derived exosomes in cardiovascular physiology and pathology.